Two - Otoshi, Kathryn (Novato, CA : KO Kids Books, 2014)
"TWO's best friend is ONE...until THREE jumps in between them. A powerful story of friendship, loss, letting go, and self-discovery"--Publisher.
4 and up.
edited hb 2015-06-16
Keywords: Counting -- Juvenile fiction; Courage -- Juvenile fiction; Friendship -- Juvenile fiction; Grief -- Juvenile fiction; Number concept in children -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; Counting -- Fiction; Courage -- Fiction; Friendship -- Fiction; Grief -- Fiction; Number concept -- Fiction; Self-actualization (Psychology) -- Fiction; Separation (Psychology) -- Fiction; Concept books; Counting books